Penatalaksanaan Isolasi Mandiri Pada Pasien Covid-19 - Eppy Setiyowati; Mulyadi Mulyadi; Umi Hanik; Arief Candra Purnama; Anis Muthaharoh; Sri Wilujeng; Madjid Madjid; Ami Ardianti (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The increase in covid 19 sufferers in some areas has increased quite significantly even deaths due to the transmission of the covid19 virus is a pandemic that is sweeping several countries including one in Indonesia. The purpose of the devotional activity is to provide health education about self-isolation treatment protocols in COVID-19 patients at dr Ramelan Hospital polyclinics Surabaya.  This approach in community service is to conduct health education by playing a video that contains about self-isolation treatment protocols in covid 19 patients. This event is held for 2 weeks (July 25 to August 10, 2021).  The final result of community service activities is an article published in a national journal and recorded in the form of learning media, namely videos and titles on patented banners (HaKI).